Evaluating the Implementation of Meaningful Participation Principles for Vulnerable Groups in Promoting Inclusive Legislation: A Comparative Study of Indonesia and Poland - Putra, Rengga Kusuma; Nugraha, Satriya; Juchnevicius, Edvardas; Naresta Hanum, Willy; Leoni Prakasa Yakub, Sandra (Kertha Patrika, 2026)
This study aims to evaluate the regulation and implementation of the principle of meaningful participation of vulnerable groups in the legislative process, and to identify factors influencing its effectiveness in realizing inclusive legislation through a comparative study between Indonesia and Poland. This study uses a normative legal research method with a legislative, conceptual, and comparative approach. The legal sources include primary legal materials in the form of constitutions, laws, and regulations related to public participation and legislation; secondary legal materials in the form of national and international scientific journals, textbooks, and reports from state and international institutions; and tertiary legal materials as conceptual support. The analysis was conducted qualitatively through legal reasoning and a comparison between norms and practices in Indonesia and Poland. The results show that normatively both countries have recognized the importance of public participation, including vulnerable groups, as part of the principles of democracy and the rule of law. However, the implementation of meaningful participation still faces gaps between regulation and practice, particularly regarding access to information, substantive involvement, and the actual influence of vulnerable groups on the substance of legislation. Factors determining the effectiveness of meaningful participation include the strength of the legal basis, the political commitment of lawmakers, institutional capacity, the role of civil society, and transparency and accountability mechanisms. This research makes a scientific contribution by enriching comparative law-based inclusive legislative studies and offering policy recommendations for strengthening meaningful participation of vulnerable groups.